Quelle position adopter face au patrimoine qui vient ? - Hervé Davodeau; Régis Barraud (Développement Durable et Territoires)
This paper is based on the findings of a research project dealing landscape heritage of the Loire valley (France). We question the position of the scientist facing what we’re calling here a ‘latent’ heritage. The first part of the paper provides a geo-historical contextualisation of the hydraulic works (groynes) intended to improve navigation (channeling). We focus on identifying and analyzing time references used over the different periods : before, during and after the initial development of the groynes and the channel. Then, we present the results of a survey work with local residents demonstrating their weak knowledge of this history by pointing out the paradoxes of their social representations of these objects. The perspective of a future controversy, we defend a position of research "based on landscape analysis" to deal with heritage and participation issues in order to debate the temporalities at work in the restoration policy of the Loire River.